Anti-lung cancer activity of Schizonepetae Spica extract and identification of its compounds by ultra-performance liquid chromatography coupled with quadrupole-time-of-flight mass spectrometry. Issue 17 (8th November 2019) - Wang, Shuai; Yang, Xinxin; Han, Xiao; Li, Tianjiao; Bao, Yongrui; Meng, Xiansheng
Abstract: Schizonepetae Spica (SS), a well-known traditional Chinese medicine has been widely used over thousands of years. In modern medicine, it has been adopted in the traditional prescription for cancer in clinic. In order to further develop the medicinal value of SS, we conducted cell viability assay and cell apoptosis research and proved that the extraction of Schizonepetae Spica (SSE) possesses prominent pharmacological activity against lung tumor. It can promote the late apoptosis of A549 cells. And the growth inhibition of SSE on A549 cells was manifested in a concentration-and time-dependent manner. Furthermore, an UPLC-QTOF-MS method was applied to identify the chemical components of SSE for the first time. A total of 30 compounds were tentatively identified, of which flavonoids and organic acids are the main ingredients. The results presented here would be helpful for the further study of plasma migration components and quality control of SS, which lay a foundation for the discovery of the pharmacodynamic basis of SSE and the development of new anti-tumor drugs. GRAPHICAL ABSTRACT: